Evidence for the founder effect of a novel ACVRL1 splice‐site mutation in Hungarian hereditary hemorrhagic telangiectasia families. Issue 5 (12th June 2016) - Major, T.; Gindele, R.; Szabó, Z.; Alef, T.; Thiele, B.; Bora, L.; Kis, Z.; Bárdossy, P.; Rácz, T.; Havacs, I.; Bereczky, Z.
Abstract :